Klounid ja teised kurjamid – hirmu ja vägivalla mitu nägu. Ostensioon ja kriminaalsed legendid - Eda Kalmre (Keel ja Kirjandus, 2024)
This article explores scary stories about evil clowns and men abducting children in white vans, which are known internationally and have recently spread among Estonian children and young people. In some cases, these narratives have transcended legend, prompting several criminal investigations in Estonia in recent years regarding alleged crimes committed by these nefarious characters. Communication among children, teenagers and young adults occurs both online and offline, i.e., by word of mouth. These age groups also engage in ostensive practices, where several forms of ostension can occur simultaneously. It is often quite challenging to discern between a mere prank, a little lie, a spontaneous experience of fear, or immersion in the story. In the cases from Harku parish, Põlva, and Viljandi, we observe how the playful social dynamics and belief systems typical of children’s and youth culture enter the public sphere through social media, transforming a criminal legend into a real criminal case. In the public sphere, the children’s stories create a different sense of danger (moral panic) and acquire a different meaning by portraying the surrounding world as dangerous and criminal. This change of context imbues the incident or legend with broader social significance and critique. The internet has intensified the seriousness of these evil character stories, providing a rich digital content that mixes various genres and activities, making them more immediate and impactful than the horror stories of the pre-internet era.